Ion exchange demineralisation for recycling of flowing rinse wastewater within printed circuit board manufacturing - Kent, Fraser C (University of Ottawa (Canada), 2003)
In the last fifty years the electronics industry experienced substantial growth. During this period of growth technologies for manufacturing printed circuit boards, the heart of most electronics, have evolved continually. These improvements include many environmentally conscious innovations within the manufacturing process. Flowing rinse systems are an essential part of the manufacturing process. These flowing rinse baths utilize a very large amount of water. Environmental benefits and economic gain can sometimes be achieved through recycling the flowing rinse effluent for reuse. Ion exchange is a conventional water treatment technology that is well suited to the application of recycling flowing rinse water from circuit manufacturing processes. This is due to the dilute nature of the solutions as well as the high proportion of ionic constituents that must be removed. Specifically, ion exchange demineralisation holds the capacity to treat flowing rinse water to a high purity allowing optimal rinsing efficiency and continual reuse of the same water. Experiments were undertaken, using a variety of ion exchange demineralisation setups and materials to prove that this technology will work for a specific application at an Ottawa circuit board manufacturer. A series of experimental runs were performed leading to the conclusion that ion exchange demineralisation is effective for the recycling of this manufacturer's flowing rinse wastewater. The Serfilco MBD-10 mixed bed resin showed the best performance although, being a mixed bed resin, it is not readily regenerated leading to a high operating cost of approximately $8.65/m3 of water treated. It is expected that a two-bed system with the same type of resins (strong acid and strong base) would have the capability of treating the same water to an acceptable level at a much lower cost and this type of set-up is recommended for future work. It was demonstrated that chelating strong acid resins such as the ones used in some of the experiments are not effective for demineralisation.
Keywords: Engineering, Chemical.; Engineering, Electronics and Electrical.